CODE MIXING IN MY STUPID BOSS NOVEL - Anita Rebekawati; Elia Masa Gintings (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
ABSTRACTThis study deals with the use of code mixing in My Stupid Boss novel. The objectives of this study was to find out the type of code mixing dominantly used and to determine whether in narrative or dialogue context does the code mixing frequently used in My Stupid Boss Novel. The source of data was the sentences of novel entitled My Stupid Boss Novel. The data were limited only in Indonesian- English code mixing used by the author my My Stupid Boss and analyzed based on the types of code mixing which are unit insertion, unit hybridization, sentence insertion, idiom and collocation insertion, reduplication. The research was conducted by using descriptive qualitative method. The findings show that all the types of code mixing occurred in My Stupid Boss; they were unit insertion 70.51 %, unit hybridization 6.13 %, sentence insertion 21.61 %, idiom and collocation insertion 1.60 % and reduplication 0.15 %. The most dominant type of code mixing was unit insertion. The code mixing was found dominantly in dialogue context 55.47 % while in narrative context 44.53 %.. It is hoped that the result of this study is useful to everyone who wants to study about code mixing.Keywords : Sociolinguistics, Code mixing, My Stupid Boss Novel________________* Graduate Status** Lecturer